Cross-temporal and cross-national poverty and mortality rates among developed countries - Johan Fritzell; Olli Kangas; Jennie Bacchus Hertzman; Jenni Blomgren; Heikki Hiilamo (Luxembourg Income Study (LIS), 2013)
A prime objective for welfare state activities is to take action to enhance population health and decrease mortality risks. Poverty has for several centuries been seen as a key social risk factor in these respects. Consequently, the fight against poverty has historically been at the forefront of public health and social policy. The relation between relative poverty rates and population health indicators is less self-evident, notwithstanding the obvious relation to the debated topic of the relation between population health and income inequality. In this study we make a comparative analysis on the relation between relative poverty and mortality across 26 countries over time with pooled cross-sectional time series analysis. We utilize data from the Luxembourg Income Study to construct age-related poverty rates across countries and time covering the period from around 1980 to 2005 merged with data on age- and gender-specific mortality data from the Human Mortality Database. Our results suggest an impact of relative poverty but also clear differences by welfare regimes that partly go beyond the well-known differences in poverty rates between welfare regimes.
Keywords: 330; Sozialpolitik; Sterblichkeit; Gesundheit; Armut; Armutsbekämpfung; Vergleich; Nordeuropa; Mitteleuropa; Nordamerika; Australien